The wedding promise [large type] - Kinkade, Thomas, 1958-2012 (Kinkade, Thomas, 1958-2012. Angel Island novel., 2011)
Liza Martin has booked a June wedding, the first major event at her inn, and hopes everything comes together after noticing tensions between the bride and groom.